Pengaruh Media Baamboozle Terhadap Minat Belajar Matematika Siswa di MI Nurul Huda - Aulia, Ghina; Amran, Amran; Saputra, Raden Ridwan Hasan (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the effect of Baamboozle learning media on the interest in learning Mathematics of class II students of MI Nurul Huda 3 Bogor. The method used is quantitative with a Quasi Experimental design, specifically Nonequivalent Control Group Design. The sample consisted of 42 students, divided into two groups: the experimental class (using Baamboozle) and the control class (without Baamboozle), 21 students each, selected through purposive sampling. The research instrument was a learning interest questionnaire. The results showed that the average posttest of the experimental class (46.8) was higher than the control class (36.5), with a significance value of 0.000 (<0.05), indicating that Ha was accepted. In conclusion, Baamboozle media has a significant effect on increasing students' interest in learning Mathematics